301 - Symposium social health: a pathway to inclusion and cognitive health: Social health, social inclusion and its associations with cognitive functioning. (October 2021) - Vernooij-Dassen, Myrra; Verspoor, Eline; Hubers, Claudia; Lenart, Marta; Wiegelman, Henrik; Perry, Marieke
Abstract : Background: Inclusion is taken as a natural situation, until feelings of exclusion are perceived. Social relations are for human beings like water to plants. Social health has been defined in 1946 by the WHO as the social domain of health. It is an umbrella concept that covers how the individual relates to his or her social environment and vice versa. Social inclusion is a key marker or characteristic of social health, represented by specific markers such as participation in leisure activities. Objective: We aim to study theoretical mechanisms and social health markers relevant to inclusion and cognitive functioning. Methods: identification of mechanistic pathways and systematic review on the relationship between combinations of social health markers and cognitive functioning and dementia in healthy older adults. Results: We combined neurobiological and social pathways to guide our study. The search for social health markers yielded 4332 potentially relevant citations. Eleven articles were eligible for inclusion. Combining social health marker reflecting social exclusion (e.g. social isolation, financial deprivation, living alone and lacking basic social rights) revealed a significant risk factor for both the development of dementia and reduced cognitive functioning. A combination of a high educational level, high occupational complexity and participating in leisure activities was protective for good cognitive functioning and dementia. Conclusion: Several social health markers are a pathway to social inclusion and to cognitive functioning, with markers reflecting exclusion being a risk factor, while those reflection inclusion are associated with protective effects. These findings open doors for interventions using the potential of social health in prevention of cognitive decline and dementia.